DAMPAK PENERAPAN REMUNERASI, MANAJEMEN PERUBAHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (STUDI PADA PEGAWAI RSUP PROF DR. R.D. KANDOU MANADO) - Megawe, Deisy Sandra; Mandey, Silvya L.; Trang, Irvan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
The organization in the era of globalization increasingly rapidly make competition in an organization is tight. Organization of the government can optimize sued for human resources and how to manage human resources. Employees are the key for organization, wealth where they will be planner implementation and control are an active role in creating the organization. Employees have mind feelings and desires that might affect on the work he was doing this attitude will determine how much love of working for him to loyalty to the organization.The purpose of this study is to find the influence of the application of remuneration, change management and organization cultural on the employee performance RSUP Prof. Dr. R.D. Kandou Manado. This research take 60 a sample of respondents in RSUP Prof. Dr. R.D. Kandou Manado, using economic research to get a response to statement and using analysis multiple linear regression assisted a statistical analysis.The results obtained the research is together there are significant influence between remuneration, change management and cultural against the employee performance of organization. A partial remuneration significant against the employee performance, change management influential significantly against the employee performance is the positive and significant between organization cultures against the employee performance RSUP Prof. Dr. R.D. Kandou Manado.Â Keywords : Remuneration, Change Management, Organization Cultures, RSUP Prof. Dr. R. D. Kandou Manado